TOTAL POLYPHENOLIC CONTENT AND ANTIOXIDANT ACTIVITY OF SILYBUM MARIANUM CULTURES GROWN ON DIFFERENT GROWTH REGULATORS - Mekky, Hattem; Sohafy, Samah El; El-khair, Rasha Abu; Hawiet, Amr El (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The present study was designed to study the effect of supplementing Silybum marianum cultures with different combinations and concentrations of growth regulators on the total phenolic content and the antioxidant activity of the produced cultures. Methods: The total polyphenolic content of 23 extracts of calli was calculated as µg of gallic acid/mg of dry weight extract (DWE) using Folin–Ciocalteu reagent. The antioxidant activity was calculated as trolox equivalent antioxidant capacity using 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) assay for extracts containing more than 10 µg gallic acid/mg DWE. Results: Most of the combinations showed an increase in the total polyphenolic concentration compared to the wild plant. However, cultures grown on media supplemented with combinations of benzyl aminopurine (BAP) and gebberellic acid (Gb), adenine (Ad) and kinetin (Kin), BAP and indole acetic acid (IAA) possessed the highest total polyphenolic contents 20.5, 13.09 and 12.15 µg gallic acid/mg DWE, respectively. However, only (BAP+Gb), (BAP+1-Naphthaleneacetic acid (NAA), IAA, kin and (BAP+Ad) showed a significant increase in the antioxidant activity calculated as trolox equivalent with 2.65, 1.56, 1.56, 1.35 and 1.22 folds increase over the wild plant, respectively. Conclusion: The results obtained clearly indicated that changing the growth regulator system of Silybum marianum cultures serves as an easy and reliable method for increasing the total phenolic content and the antioxidant activity of cultures.